Cost Analysis of the STONE Randomized Trial: Can Health Care Costs be Reduced One Test at a Time?. Issue 4 (April 2016) - Melnikow, Joy; Xing, Guibo; Cox, Ginger; Leigh, Paul; Mills, Lisa; Miglioretti, Diana L.; Moghadassi, Michelle; Smith-Bindman, Rebecca
Abstract : Background: Decreasing the use of high-cost tests may reduce health care costs. Objective: To compare costs of care for patients presenting to the emergency department (ED) with suspected kidney stones randomized to 1 of 3 initial imaging tests. Research Design: Patients were randomized to point-of-care ultrasound (POC US, least costly), radiology ultrasound (RAD US), or computed tomography (CT, most costly). Subsequent testing and treatment were the choice of the treating physician. Subjects: A total of 2759 patients at 15 EDs were randomized to POC US (n=908), RAD US, (n=893), or CT (n=958). Mean age was 40.4 years; 51.8% were male. Measures: All medical care documented in the trial database in the 7 days following enrollment was abstracted and coded to estimate costs using national average 2012 Medicare reimbursements. Costs for initial ED care and total 7-day costs were compared using nonparametric bootstrap to account for clustering of patients within medical centers. Results: Initial ED visit costs were modestly lower for patients assigned to RAD US: 423 (411, 434) compared with patients assigned to CT: 448 (438, 459) ( P <0.0001). Total costs were not significantly different between groups: 1014 (912, 1129) for POC US, 970 (878, 1078) for RAD US, and 959 (870, 1044) for CT. Hospital admissions contributed over 50% of total costs, though only 11% of patients were admitted. Mean total costs (and admission rates) varied substantially by site from 749 to 1239. Conclusions: Assignment to a less costly test had no impact on overall health care costs for ED patients. System-level interventions addressing variation in admission rates from the ED might have greater impact on costs.